Critical issues in human ecology - Dixie, Philip Oswald Strathmore (Department of Sociology, 2016)
Formally stated, the subsequent analysis aims at identifying systematically some issues in Classical Human Ecology and discussing them in the light of methodological criteria derived from the above mentioned sources. It is hoped that this discussion will contribute to a more systematic evaluation of criticisms or issues in Classical Human Ecology; prove to be of some use in providing constraints in contributions to Modern Ecology.